Neuroprotective Effects of Lactoferrin in Alzheimer's and Parkinson's Diseases: A Narrative Review - Yong, Shin Jie *; Abhi, Veerakumarasivam *; Lim, Wei Ling *; Chew, Jactty *; abhi, (American Chemical Society, 2023)
Recent advancements in lactoferrin research have uncovered that lactoferrin does function not only as an antimicrobial protein but also as an immunomodulatory, anticancer, and neuroprotective agent. Focusing on neuroprotection, this literature review delineates how lactoferrin interacts in the brain, specifically its neuroprotective effects and mechanisms against Alzheimer’s and Parkinson’s diseases (AD and PD), the two most common neurodegenerative diseases. The neuroprotective pathways involving surface receptors (heparan sulfate proteoglycan (HSPG) and lactoferrin receptor (LfR)), signaling pathways (extracellular regulated protein kinase-cAMP response element-binding protein (ERK-CREB) and phosphoinositide 3-kinase/Akt (PI3K/Akt)), and effector proteins (A disintegrin and metalloprotease10 (ADAM10) and hypoxia-inducible factor 1α (HIF-1α)) in cortical/hippocampal and dopaminergic neurons are described. These cellular effects of lactoferrin are likely responsible for attenuating cognitive and motor deficits, amyloid-β and α-synuclein accumulation, and neurodegeneration in animal and cellular models of AD and PD. This review also discusses the inconsistent findings related to the neuroprotective effects of lactoferrin against AD. Overall, this review contributes to the existing literature by clarifying the potential neuroprotective effects and mechanisms of lactoferrin in the context of AD and PD neuropathology.